1997
DOI: 10.1095/biolreprod57.1.204
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and translation in bovine nuclear transfer embryos

Abstract: The development of bovine embryos reconstructed by nuclear transfer (NT) is poor compared to that of embryos produced by in vitro fertilization. One reason for this could be incomplete reprogramming of the transferred nucleus. Therefore, with a view to optimizing the conditions for NT, the reprogramming of blastomere nuclei from 16- to 32-cell-stage in vitro-fertilized (IVF) embryos was investigated following NT by fusion of individual blastomeres with cytoplasts prepared from oocytes at two different stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 43 publications
3
21
0
2
Order By: Relevance
“…The present study also provides evidence for nuclear localization of TBP protein during bovine embryo development just prior to MET, suggesting its involvement in MET in the bovine species as well. However, a low amount of TBP protein was detected in the nucleus of earlier stage embryos, which could be related to the faint transcription detected in these stages (Barnes & First 1991, Plante et al 1994, Lavoir et al 1997, Memili et al 1998, Natale et al 2000. Therefore, the intensifying signal of TBP in the nucleus of late 8-and 16-cell embryos concomitant with the disappearance of YBX2 provides evidence in support of the major genome activation in the bovine occurring at the 8-to 16-cell stage.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The present study also provides evidence for nuclear localization of TBP protein during bovine embryo development just prior to MET, suggesting its involvement in MET in the bovine species as well. However, a low amount of TBP protein was detected in the nucleus of earlier stage embryos, which could be related to the faint transcription detected in these stages (Barnes & First 1991, Plante et al 1994, Lavoir et al 1997, Memili et al 1998, Natale et al 2000. Therefore, the intensifying signal of TBP in the nucleus of late 8-and 16-cell embryos concomitant with the disappearance of YBX2 provides evidence in support of the major genome activation in the bovine occurring at the 8-to 16-cell stage.…”
Section: Discussionmentioning
confidence: 93%
“…However, subsequent studies have shown that some transcription also occurs in earlier stages, in the two-or four-cell embryos (Barnes & First 1991, Plante et al 1994, Lavoir et al 1997, Memili et al 1998, Natale et al 2000. However, this early transcription is slighter and the major activation of transcription still appears to occur in the eight-cell-stage embryos.…”
Section: Introductionmentioning
confidence: 99%
“…These observations were made following transfer of embryonic (Stice and Robl 1988;Prather et al 1989;Collas and Robl 1991;Kanka et al 1991) as well as somatic (Czolowska et al 1984) nuclei. Global changes in transcriptional activity of the transplanted nuclei have also been observed Schultz et al 1996;Smith et al 1996;Lavoir et al 1997). Expression analysis using RT-PCR revealed similar patterns of transcription between clones and fertilized embryos in porcine (␤-actin-GFP; Koo et al 2001) and bovine preimplantation embryos (TEC-3;van Stekelenburg-Hamers et al 1994);Oct4, FGF2, FGFr2, gp130, and poly(A) polymerase (Daniels et al 2000); lactate dehydrogenase (LDH), citrate synthase, and phosphofructokinase (PFK; Winger et al 2000).…”
mentioning
confidence: 87%
“…The transcription resumed thereafter in 2-cell stage embryos and rapidly increased at 16-cell stage, reaching the transcriptional level typically as that of the 32-cell stage nuclei used for the transfer. In bovine, Lavoir et al [3] transferred nuclei of 16-to 32-cell stages in vitro-fertilized embryos into enucleated oocytes and they found that the hnRNA production in nuclear transfer embryos was much higher than that in control in vitro-fertilized embryos at 1 to 4-cell stages. They concluded that it was because the reprogramming of the transferred nuclei was absent or incomplete that the patterns of Zhu et al [4] initiated transgenic studies in fish and generated the "model of transgenic fish" [5] subsequently.…”
mentioning
confidence: 99%